Когнитивный подход к анализу художественного текста (Scientific journal of the Fergana State University, 2024)
The article is devoted to the consideration of a cognitive approach to the analysis of a literary text. The connection between cognitive linguistics and cognitive stylistics, which share categorical concepts – conceptualization, categorization, nomination, concept, is highlighted. These concepts are fundamental in interpreting the text from a cognitive point of view, which is the object of the article. The relevance of the work is confirmed by the need to highlight the procedure for step-by-step modeling of the cognitive interpretation of a literary text, which was not previously presented in a structured way in scientific papers. Having considered the main concepts of cognitive linguistics and stylistics, the most essential concepts for the cognitive analysis of a literary text were identified – concept, conceptualization, categorization, knowledge structures, cognitive principles of information distribution in the text and frame. The most optimal way to represent the cognitive structure of a text is the cognitive analysis of the conceptual sphere and frames of a literary text, which represents a step-by-step procedure: the search for verbal signals representing conceptually important frames; deciphering the semantics of frames; activation of knowledge structures and conceptualization of textual information. Using the example of the cognitive analysis of the short story “The Mockingbird” by Ambrose Bierce, it was shown that through the involvement of cognitive actions, the highest degree of understanding of the text is achieved in the process of its interpretation.